Factors affecting organized customers' satisfaction with digital banking service quality of commercial banking in Ho Chi Minh city - Phan, Thị Cúc; Do, Đoan Trang; Vu, Tiến Đạt (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
The benefits of digital banking make every transaction more accurate, fast and secure. This study aims to determine the satisfaction of elderly customers when using digital banking services of commercial banks in Ho Chi Minh City and at the same time determine the influence of factors from which makes appropriate management implications. The results of the survey and analysis of 267 survey samples of elderly customers show that there are 6 factors affecting the satisfaction of elderly customers and are arranged in descending order as follows: 1) Tangible means ; 2) Service capacity; 3) Ease of use; 4) Responsiveness; 5) Reliability; 6) Empathy. Since then, the authors have proposed six managerial implications to improve the satisfaction of elderly customers with the quality of digital banking services of commercial banks in Ho Chi Minh City.